2018
DOI: 10.1155/2018/1901896
|View full text |Cite
|
Sign up to set email alerts
|

The Value of MRI in Distinguishing Subtypes of Lipomatous Extremity Tumors Needs Reassessment in the Era of MDM2 and CDK4 Testing

Abstract: Introduction Extremity lipomas and well-differentiated liposarcomas (WDLs) are difficult to distinguish on MR imaging. We sought to evaluate the accuracy of MRI interpretation using MDM2 amplification, via fluorescence in-situ hybridization (FISH), as the gold standard for pathologic diagnosis. Furthermore, we aimed to investigate the utility of a diagnostic formula proposed in the literature. Methods We retrospectively collected 49 patients with lipomas or WDLs utilizing MDM2 for pathologic diagnosis. Four ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 17 publications
(52 reference statements)
1
16
0
Order By: Relevance
“…ALTs account for approximately 25% of all deep lipomatous tumors of the extremities and are most frequently located in the thigh [ 8 ]. Historically, ALTs were difficult to distinguish from benign lipomas as the two lesions have an overlapping gross, histologic, and radiologic appearance [ 9 , 10 ]. However, the recent identification of amplification of the MDM2 oncogene in ALTs has facilitated accurate differentiation from benign lipomas.…”
Section: Introductionmentioning
confidence: 99%
“…ALTs account for approximately 25% of all deep lipomatous tumors of the extremities and are most frequently located in the thigh [ 8 ]. Historically, ALTs were difficult to distinguish from benign lipomas as the two lesions have an overlapping gross, histologic, and radiologic appearance [ 9 , 10 ]. However, the recent identification of amplification of the MDM2 oncogene in ALTs has facilitated accurate differentiation from benign lipomas.…”
Section: Introductionmentioning
confidence: 99%
“…However, MR imaging features have documented only moderate accuracy for predicting the final diagnosis, compared to pathology. Ryan at al (12) suggested that the accuracy is in the region of 73% Therefore, there is a requirement to improve the differentiation of these entities noninvasively using MRI. In the present study, we evaluated intra-tumoural heterogeneity using MRI radiomics-based textual analysis to discriminate lipoma from ALT/WDL.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, fluoresence in situ hybridisation (FISH) identification of murine double minute 2 (MDM2) gene amplification has become the gold standard for diagnosis of ALT/WDLs (9-11). There have been several studies assessing the ability of magnetic resonance imaging (MRI) to differentiate these lesions (12,13). The previously well documented MRI accuracy for distinguishing these two tumours is in the region of 70% (12), with suggested reliable imaging discriminators being size and lipomatous content (13).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations